Gender unemployment in the Czech and Polish labour market - Ryczkowski, Maciej; Zinecker, Marek (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
Making use of EU-Labour Force Survey data, the authors estimated logistic regressions with a maximum likelihood method and found that gender unemployment risk was largely explained by human capital, marital status, receiving financial support, job experience and gender discrimination in both Poland and the Czech Republic. The gender unemployment risk gap amounted to 8% and 10% in Poland and the Czech Republic, respectively. Although the impact of marital status was significant and considerable, married women in the Czech Republic benefited from their marital status on average three times less than men in the Czech Republic, and men and women in Poland. In both countries only women aged below 30 were ‘rewarded’, while women beyond 50 years of age were penalized in terms of unemployment risk. As opposed to that, men up to 60 years old have their unemployment risk reduced all else equalled. The authors argue that this form of possible discrimination in some respects is a better measure of injustice than the commonly used pay gap and it constitutes an alternative dimension of ‘gender inequality’. The results can contribute to better targeted policies against discriminatory practices by enhancing the career paths demanded in the labour market and by breaking the stereotypes rooted in the cultures of Polish and Czech societies
Argumenta Oeconomica, 2020, Nr 2 (45), s. 213-229
Keywords: gender discrimination; unemployment risk; gender unemployment gap; Poland; Czech Republic